Hubungan Subjective well-being dengan Loneliness Terhadap Anak Panti Asuhan Baitul Hidayah Al Mukaramah di Kota Padang - Messy Mardatillah; Mario Pratama (CAUSALITA : Journal of Psychology, 2026)
Not all teenagers expect to live in an orphanage, but there are some who have to stay there for various reasons. Life in an orphanage is also very complex with many problems occurring, especially for teenagers who are still unstable and entering a transitional period. The aim of this study is to examine the relationship between subjective well-being and loneliness among children at the Baitul Hidayah Al Mukaramah Orphanage in Padang City. This research uses a quantitative method. The instrument used is a questionnaire with a Likert scale to measure the relationship between subjective well-being and loneliness among children at the Baitul Hidayah Al Mukaramah Orphanage in Padang City. However, the results of the study indicate that there is no significant relationship between subjective well-being and loneliness among children at the Baitul Hidayah Al Mukaramah Orphanage in Padang City. According to data analysis in the form of Pearson Correlation with the assistance of the SPSS Statistics computer program. The relationship between the two variables is not strong enough to be considered statistically significant because the P value is greater than 0.05, specifically 0.235. However, this study provides important insights into understanding the relationship between subjective well-being and loneliness in orphaned children. Further research is recommended using a larger sample, and various intervention methods are necessary to gain a better understanding. In addition, it is suggested to review the design and implementation of the program, as well as consider other factors that may influence the effectiveness of the intervention, such as program duration, number of subjects, and additional training methods.